Position guidelines and evidence base concerning determinants of childhood obesity with a European perspective. (19th November 2021) - Martinez, J. Alfredo; Sassi, Franco; Moreno, Luis A.; Tur, Josep A.
Summary: Childhood obesity is one of the most pressing global public health issues, with rates increasing fastest in countries at low levels of income. Obesity occurring during childhood is likely to persist throughout the life course, and it is a cause of increased disease risk from the early years of life. This supplement is the result of collaborations involving a large and multidisciplinary group of researchers that were established in the context of the ongoing European Horizon 2020 project Science and Technology in childhood Obesity Policy (STOP). The aim, as in the entire STOP project, is to generate evidence that can support better policies to tackle the problem of childhood obesity in Europe and elsewhere. Quality of life and health well‐being concerning children needs to consider personalized, population, and planetary facets to tackle childhood obesity at early stages of life, for in‐deep phenotyping, integrating personalized medicine and precision public health interventions at global levels. This supplement contributes to this aim.